Effects of phillyrin and forsythoside A on rat cytochrome P450 activities in vivo and in vitro. (3rd April 2017) - Cheng, Yanwen; Liang, Xiaoling; Feng, Liying; Liu, Duo; Qin, Mengnan; Liu, Shuang; Liu, Gaofeng; Dong, Mei
Abstract: 1. Phillyrin and forsythoside A are two important active ingredients in Forsythia suspensa . However, the effects of phillyrin and forsythoside A on the activities of cytochrome P450 (CYP450) remain unclear. 2. This study aimed to investigate the effects of phillyrin and forsythoside A on the activities of CYP1A2, CYP2C11, CYP2D1 and CYP3A1/2 by cocktail probe drugs in rats both in vivo and in vitro . 3. Many pharmacokinetic parameters of caffeine and metoprolol in phillyrin pretreatment group, caffeine and tolbutamide in forsythoside A pretreatment group were affected significantly. In rat liver microsomal incubation system, the concentrations of acetaminophen and dextrophan in the phillyrin pretreatment group are higher than blank control group by 207.69% and 125.00%, however, the concentrations of 4-hydroxytolbutamide and 6β-hydroxytestosterone were not significantly altered. The concentrations of acetaminophen and 4-hydroxytolbutamide in the forsythoside A pretreatment group are higher than blank control group by 223.07% and 154.16%, whereas the concentrations of dextrophan and 6β-hydroxytestosterone were not significantly altered. 4. These results indicated that Phillyrin had potential inductive effects on rat CYP1A2 and CYP2D1 activities, without affecting CYP2C11 and CYP3A1/2 activities. Moreover, forsythoside A had inductive effects on the activities of CYP1A2 and CYP2C11, without affecting CYP2D1 and CYP3A1/2 activities.